Contribution of Mobile Teams to Efforts to Eliminate Schistosomiasis at Schistosoma haematobium in Morocco- Narrative Review Article. - Hicham Barkia; Abdelaziz Barkia; Rajae Yacoubi; Ali Alemad; Khadija El Kharim; Driss Belghyti (Tehran University of Medical Sciences, 2014)
Since it was first diagnosed in 1914 in Marrakesh, schistosomiasis has been a public health problem in Morocco for decades. A national control program launched in 1982 has led to a considerable reduction in the incidence and morbidity associated with the disease. Consequently, the program has shifted from disease control to an elimination process launched in 1994. This process aimed to eliminate disease transmission by the end of 2004 and has helped to clear all known foci. Mobile teams were a key element that contributed to the success of this program. They played three important roles: monitoring and control, response, and the transmission of messages.